The Diagnostic Value of the Combined 3D Pseudo-Continuous Arterial Spin Labeling and Diffusion Kurtosis Imaging in Patients With Binswanger’s Disease - He, Xiaoyi; Dou, Weiqiang; Shi, Hao (Frontiers in Neuroscience, 2022)
Background and purpose: The clinical diagnosis of Binswanger’s disease (BD), a chronic progressive form of subcortical vascular dementia, remains challenging. 3D pseudo-continuous arterial-spin-labeling (pcASL) and diffusion kurtosis imaging (DKI) can quantitatively reveal the microcirculation changes and heterogeneity of white matter (WM), respectively. We thus aimed to determine the diagnostic value of the combined 3D-pcASL and DKI in BD. Materials and methods: Thirty-five BD patients and thirty-three healthy controls underwent 3D-ASL and DKI experiments. The perfusion parameter of cerebral blood flow (CBF), diffusion parameters of fractional anisotropy (FA), mean/axial/radial diffusivity (MD/Da/Dr), and kurtosis parameters of anisotropy fraction of kurtosis (FAk) and mean/axial/radial kurtosis MK/Ka/Kr were obtained to quantitatively measure the parametric distributions of functional brain sub-regions. One-way analysis of variance and post-hoc T-test were applied to explore the different distributions of DKI/ASL-derived parameters among brain sub-regions of BD. In addition, all region-specific DKI/ASL parameters were separately analyzed in Pearson correlation analysis to investigate the relationship with Mini-mental State Examination (MMSE), a typical clinical scale for cognitive function assessment in BD patients. Results: FA/FAk/MK/Ka/Kr were significantly declined in all WM hyperintensities (WMHs) of BD compared with healthy controls, while the corresponding MD/Da/Dr were significantly increased (all p < 0.005). In addition, significant changes, similar to the WMHs of BD patients, were also observed in almost all DKI parameters in WM normal areas and genu/splenium of the corpus callosum (GCC/SCC) in BD (p < 0.005). Finally, CBF was significantly reduced in all of the above regions we measured in BD patients (p < 0.005). For BD patients, MMSE showed negative correlation with MD/Da in thalamus (r=-0.42/-0.58; p<0.05), and positively correlated with CBF in PWM/TWM (r=0.49/0.39; p<0.05). Using ROC analysis, FA/FAk/Kr in GCC, CBF/FA/Dr/FAk in SCC, MD/Da/Ka in thalamus, and the combined FA/MD/Dr/CBF in TWM showed high accuracy (AUCs 0.957/0.946/0.942/0.986) in distinguishing BD patients from healthy controls. Conclusions: We found that combined DKI and 3D-ASL are helpful in diagnosing BD patients, especially with FA, MD, Dr and CBF in temporal WM region. Additionally, the kurtosis parameters of DKI can sensitively monitor the potentially damaged WM areas in BD patients, adding complementary clinical value.